Islamic tax (Al-Khums) in jurisprudence and economic equity / Mohd Solahuddin Shahruddin ... [et al.] - Shahruddin, Mohd Solahuddin; Ismail, Ahmad Zuhdi; Mohamad Zaini, Mohd Norazri; Abdullah, Mohd Yusra; Norman, Mohd Paidi; Mohd Noor, Muaz (Universiti Teknologi MARA, 2024)
This paper aims to provide a comprehensive understanding of the concept of al-Khums in Islamic law. Al-Khums refers to the religious obligation of Muslims to pay one-fifth of their surplus income to religious authorities. The paper explores the basis for al-Khums in the Quran, its historical development, and its practical application in various aspects of Muslim society. Additionally, it examines the controversies and debates surrounding al-Khums and its relevance in contemporary times. The study employs a review analysis methodology to investigate al-Khums, emphasizing its historical context, foundational principles, and contemporary applications. By thoroughly analyzing primary and secondary sources, this paper aims to highlight the significance and implications of al-Khums in Islamic law.